Composites with micro- and nano-structure computational modeling and experiments - Kompiš, Vladimír. (Computational Methods in Applied Sciences,, 2008)
This book contains selected, extended papers presented in the thematic ECCOMAS conference on Composites with Micro- and Nano-Structure (CMNS) – Computational Modelling and Experiments held in Liptovský Mikuláš, Slovakia, in May 28 to 31, 2007, as well as three other papers. Recent experimental and computational results demonstrate that materials reinforced with stiff particles and fibres can obtain substantial improvements in stiffness, thermal conductivity and electro-magnetic properties. Materials reinforced with fibres can have very different properties in different directions. With these new materials the importance of computational simulations and experimental verifications also increases. The book contains atomistic and continuum numerical methods and experimental validation for composite materials reinforced with particles or fibres, porous materials, homogenization and other important topics for research in this field.